Regional aspects of state regulation of the agrarian sector of economy of the Republic of Adygea - A. A. Mokrushin (Новые технологии)
The article reveals the problems of state regulation and support of the agrarian sector of economy of the Republic of Adygea. The characteristic features, tools of state regulation of agrarian sphere of economy of the Republic of Adygea are revealed. Special attention is paid to the specifics of target and departmental programs of state support of the agro-industrial complex of the Republic of Adygea, organizational and methodological problems of their development and implementation.